Energy metabolism of growing blue foxes - Koskinen, Nita; Tauson, Anne-Helene (SE, 2009)
The blue fox (Alopex lagopus) is presently the most important species in fur farming in Finland. In recent years selective breeding has focused on producing heavy animals. At present blue foxes are fed ad libitum during the growing - furring period. The blue fox exhibits seasonal fluctuations in feed intake and accretion of body fat, feed intake and body fat retention being very high during autumn and early winter if fed unrestrictedly. The main objective of this project was to establish baseline data on the energy requirement of growing blue foxes. Sixteen juvenile blue fox vixens were used and they were fed the same conventional diet. The animals were allocated to four different groups and given different energy supply in order to establish a population of animals with very different body condition. The experiment was performed in five 7d balance periods, starting when the animals were about 10 weeks old and ending when the animals were about 30 weeks old. Each period included a 22 hr respiration experiment by means of indirect calorimetry. Mean live weights in groups were similar 4.81 -5.09 kg at the beginning of the trial. At the end of the trial the mean weights in the groups were from 9,23 kg to 12.83 kg. The feed consumption was different in the groups and the animals' live weight increased according to the energy supply. Animals were growing during the trial so the period had an effect on mean live weights in all groups. Further results on heat production, energy and protein metabolism will be presented at the congress.